2022
DOI: 10.1021/acsomega.1c06990
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolite, Myo-inositol, Inhibits Catalase Activity: A Mechanism of the Distortion of the Antioxidant Defense System in Alzheimer’s disease

Abstract: A strong correlation between brain metabolite accumulation and oxidative stress has been observed in Alzheimer’s disease (AD) patients. There are two central hypotheses for this correlation: (i) coaccumulation of toxic amyloid-β and Myo-inositol (MI), a significant brain metabolite, during presymptomatic stages of AD, and (ii) enhanced expression of MI transporter in brain cells during oxidative stress-induced volume changes in the brain. Identifying specific interactive effects of MI with cellular antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Beneficial effects of myo -inositol in depression and anxiety phenotypes have been reported ( 42 , 43 ). On the contrary, myo -inositol has been described to be accumulated in the brain of people with Down’s syndrome and patients diagnosed with Alzheimer’s disease including adults with Down’s syndrome, and may contribute to pathology ( 44 47 ). Studies to guide dietary recommendations to balance myo -inositol across life stages with consideration of disease conditions are therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of myo -inositol in depression and anxiety phenotypes have been reported ( 42 , 43 ). On the contrary, myo -inositol has been described to be accumulated in the brain of people with Down’s syndrome and patients diagnosed with Alzheimer’s disease including adults with Down’s syndrome, and may contribute to pathology ( 44 47 ). Studies to guide dietary recommendations to balance myo -inositol across life stages with consideration of disease conditions are therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The identity of the inhibitory substance(s) and its origin, whether it is a component(s) of culture media or a cell-derived factor, is currently unknown. Standard components of cell culture media, such as vitamins and sodium pyruvate, have been shown to inhibit the activity of various enzymes ( 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ). Inorganic anions in culture media, serum added to media, and lactate produced by cells could all reduce the effective concentration of calcium ( 35 ), a necessary factor for TMEM2 activity ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MIN has been shown to be involved in the regulation of ROS biosynthesis and antioxidant enzyme activity in plants [47], animals [48] and humans [49]. In addition, it was shown that methyl derivatives of inositol, such as D-pinitol (3-O-methyl-D-chiroinositol (PIN)) and L-quebrachitol (2-O-methyl-L-inositol), also have free radical scavenging properties [50,51].…”
Section: And Can Increasementioning
confidence: 99%